Quantification of internal and external training load during a training camp in senior international female footballers. Issue 1 (2nd January 2022) - Doyle, Brian; Browne, Declan; Horan, Dan
ABSTRACT: Objective: This study aimed to quantify the internal and external training load profile of an international training camp and identify any differences between positional groups or starting status. Methods: 18 players were sampled using a global positioning system (GPS) and internal training load (TL) via session rate of perceived exertion (RPE). Results: Internal and external training load variation was present across all six individual training sessions. Results indicated match day −7 (MD-7), had significantly ( P = 0.001) less training volume (3339.5 m) than all other training sessions. MD-5 and MD-2 were the most intense (387.5 and 201 m very high speed running (VHSR) and 187.5 and 49 m sprint distance (SPD) respectively in combination with large volume (5933.5 and 5151.5 m). Differences in playing position and starting status were observed in MD-2. Forwards (FW) covered significantly greater distances of VHSR ( P = 0.008) and SPD ( P = 0.008) in comparison to midfielders (MF) whilst starters reported significantly (P = 0.013) higher internal training loads (TL). Conclusion: This study provides the first report on training load in elite female footballers during an international training camp including a competitive fixture highlighting the undulation of training loads across the individual training sessions, playing positions and starting status.